A deficiência de tiamina e niacina como fator de risco para doenças neurológicas - Oliveira, Nayrene Amorin Carvalho (2019)
Niacin and thiamine, vitamins obtained through diet, are precursors of coenzymes of the intermediate metabolism. The objective of the present study was to review the literature on these vitamins in oxidative metabolism and its implications for neurological diseases. The methodology consisted of a bibliographic search in the Medline and Science Direct databases, using the descriptors “oxidative stress”, deficiency, “basal metabolism”, “nervous system”, “thiamine” and “niacin”. Ten articles were obtained for the production of the review and the studies showed that the deficiency of those vitamins can cause dysfunction in the central nervous system due to different alterations in oxidative metabolism.